Merdeka Belajar in the View of Ki Hadjar Dewantara and Its Relevance for the Development of Character Education - Pujilestari, Pujilestari; Suastra, I Wayan (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aims to describe how Merdeka learns in the view of Ki Hadjar Dewantara and its relevance for character education developers. Character education is very important and must be carried out, because it forms the character of the nation which is one of the objectives of a national education. Character education is not new, but in its implementation efforts educators and educational units are still not optimally implementing character education. Nevertheless, character education continues to be pursued until today, character education continues to be implemented, strengthened, and continues to be developed including in the independent curriculum through the character of Pancasila students. Philosophically, character building through character education is needed and needs to be given to students to achieve the nation's educational goals. In line with the view of Ki Hajar Dewantara, education will not be separated from the values of character (ethics), physical, and mind of students who will later become 'humans' in society. So that character education has an important role to develop the potential of students and become a virtuous Indonesian society. In this study, the literature review method was used. This method addresses information published in a particular field of study within a specific period. A literature review can be a simple summary of sources, but usually has an organizational pattern and incorporates summary and synthesis. The data collection technique is to search for relevant journals or books. The data analysis technique used is the theory of Miles and Huberman which includes the stages of data reduction, data presentation and conclusions.